Peliosanthes gulinqingensis (Asparagaceae), a new species from Yunnan, Southwestern China - Chen, Kang; Pan, Xiang Ru; Sun, Yi Fei; Yuan, Juan Juan; Feng, Hui Zhe (Phytotaxa, 2025)
Peliosanthes gulinqingensis from south-eastern Yunnan Province of China is described here as new to science. It somewhat resembles P. crassicoronata in sharing drooping bowl-shaped purplish flowers with a hemispheric corona and corona internally thickly ribbed and ovary base hexagonal, but is readily distinguishable by the smaller leaves with fewer longitudinal veins, long-conoid pistil ca. 5.5 mm long, 6-prismatic ovary ca. 3.5 mm long possessing six wings and distinct style.